Guaranteeing safer consumption of nutraceutical products in Malaysia: must it always be on the government? - Abdul Ghani Azmi, Ida Madieha; Abd. Jalil, Juriah; Ismail, Suzi Fadhilah; Daud, Mahyuddin (2017)
Nutraceutical products have become widespread phenomenon for proclaimed benefits they seem to offer. To define what nutraceutical is has always been confusing in certain jurisdictions especially Malaysia. Legally, they cannot be considered as mere food, and they are not pharmaceutical drugs either. Due to uncertainty in its categorisation, manufacturing and product delivery processes have become easier for nutraceutical manufacturers. They have made numerous health claims that were not based on clinical evidence and there is no legal requirement for such. Although some consumers have benefited from the products, established research suggested that consumers could risks their health through long-term consumption. Hence, this paper intends to discover regulatory issues and challenges encountered by the National Pharmaceutical Regulatory Authority (NPRA) and the Food Safety and Quality Division (FSQD) under the Ministry of Health Malaysia in regulating nutraceutical products – from production to marketing processes to ensure safer consumption. Focus group discussions have been conducted with officers from NPRA and FSQD, which led to the following results. This paper finds two intriguing discovery namely: - (1) there is an ineffective self-regulatory framework governing nutraceutical industry in Malaysia as both agencies aforementioned have no effective control particularly in key areas such as enforcement, product labelling, and advertising. Secondly, the paper also finds lack of awareness and knowledge on safe production amongst nutraceutical manufacturers – which could be reflected on the products they produce and may threatens consumers in the longer run. It seems that in the Malaysian atmosphere, governmental intervention may be highly required to guarantee safer consumption of nutraceutical products – so that consumers may truly benefit from them. Self-regulation as practiced may have made the nutraceutical industry too complacent hence have placed consumers’ safety at stake.